Involvement of AMPK, IKβα-NFκB and eNOS in the sildenafil anti-inflammatory mechanism in a demyelination model - Nunes, Ana Karolina Santana; Rapôso, Catarina [UNESP]; Rocha, Sura Wanessa Santos; Barbosa, Karla Patrícia de Sousa; Luna, Rayana Leal de Almeida; Cruz-Höfling, Maria Alice da; Peixoto, Christina Alves (Elsevier B. V., 2015)
Sildenafil (Viagra®) has recently been found to have a neuroprotective effect, which occurs through the inhibition of inflammation and demyelination in the cerebellum. However, the mechanism of action of sildenafil remains unknown. AMPK, the regulatory protein of the lipid and glucose metabolism, plays a protective role by activating the eNOS enzyme. The production of a nanomolar concentration of NO by eNOS has an anti-inflammatory effect through the cGMP signaling pathway and plays an important role in the regulation of the nuclear transcription factor (NFkB), preventing the expression of inflammatory genes. The present study investigated whether AMPK-eNOS-NO-cGMP-IКβα-NFkB is involved in the mechanism of action of sildenafil in a cuprizone-demyelination model. Neuroinflammation and demyelination induced by cuprizone in rodents have been widely used as a model of MS. In the present study, five male C57BL/6 mice (7-10 weeks old) were used. Over a four week period, the groups received: cuprizone (CPZ) 0.2% mixed in feed; CPZ in the diet, combined with the administration of sildenafil (Viagra®, Pfizer, 25mg/kg) orally in drinking water, starting concurrently (sild-T0) or 15 days (sild-T15) after the start of CPZ. Control animals received pure food and water. The cerebella of the mice were dissected and processed for immunohistochemistry, immunofluorescence (frozen), western blotting and dosage of cytokines (Elisa). CPZ induced an increase in the expression of GFAP, IL-1β TNF-α, total NFkB and inactive AMPK, and prompt microglia activation. CPZ also induced a reduction of IKβα. The administration of sildenafil reduced the expression of the pro-inflammatory cytokines IL-1β and TNF-α and increased the expression of the anti-inflammatory cytokine IL-10. In addition, the administration of sildenafil reduced expression of GFAP, NFkB, inactive AMPK and iNOS, and increased IKβα. Interestingly, sildenafil also reduced levels of NGF. In general, the sild-T0 group was more effective than sild-T15 in improving clinical status and promoting the control of neuroinflammation. The present study offers evidence that sildenafil has anti-inflammatory and neuroprotective effects, which are probably achieved through modulation of AMPK-IKβα-NFκB signaling. In addition, eNOS may play a role in the sildenafil neuroprotective mechanism, contributing to the activation of AMPK. However, other pathways such as MAPK-NFkB and the downstream proteins AMPK (AMPK-SIRT1-NFκB) should also be further investigated. An understanding of these mechanisms of action is critical for the clinical use of sildenafil to control neuroinflammation in neurodegenerative diseases such as MS.
Keywords: Ampk; Cuprizone; Demyelination; Nfkb; Neuroinflammation; Sildenafil